Population Genetics of Brook Trout in the Southern Appalachian Mountains. Issue 2 (7th January 2022) - Kazyak, David C.; Lubinski, Barbara A.; Kulp, Matt A.; Pregler, Kasey C.; Whiteley, Andrew R.; Hallerman, Eric; Coombs, Jason A.; Kanno, Yoichiro; Rash, Jacob M.; Morgan, Raymond P.; Habera, Jim; Henegar, Jason; et al.
Abstract: Broad‐scale patterns of genetic diversity for Brook Trout Salvelinus fontinalis remain poorly understood across their endemic range in the eastern United States. We characterized variation at 12 microsatellite loci in 22, 020 Brook Trout among 836 populations from Georgia, USA, to Quebec, Canada, to the western Great Lakes region. Within‐population diversity was typically lower in the southern Appalachian Mountains relative to the mid‐Atlantic and northeastern regions. Effective population sizes in the southern Appalachians were often very small, with many estimates less than 30 individuals. The population genetics of Brook Trout in the southern Appalachians are far more complex than a conventionally held simple "northern" versus "southern" dichotomy would suggest. Contemporary population genetic variation was consistent with geographic expansion of Brook Trout from Mississippian, mid‐Atlantic, and Acadian glacial refugia as well as differentiation among drainages within these broader clades. Genetic variation was pronounced among drainages (57.4% of overall variation occurred among 10‐digit hydrologic unit code [HUC10] units or larger units) but was considerable even at fine spatial scales (13% of variation occurred among collections within HUC12 drainage units). Remarkably, 87.2% of individuals were correctly assigned to their collection of origin. While comparisons with fish from existing major hatcheries showed impacts of stocking in some populations, genetic introgression did not overwhelm the signal of broad‐scale patterns of population genetic structure. Although our results reveal deep genetic structure in Brook Trout over broad spatial extents, fine‐scale population structuring is prevalent across the southern Appalachians. Our findings highlight the distinctiveness and vulnerability of many Brook Trout populations in the southern Appalachians and have important implications for wild Brook Trout management. To facilitate application of our findings by conservation practitioners, we provide an interactive online visualization tool to allow our results to be explored at management‐relevant scales.